Library education in the English-speaking Caribbean - Collings, Dorothy (1973)
This article examines the professional training of librarians in the Caribbean. It discusses the creation of a library school and reviews the development of library services in the region, with special reference to Jamaica. The potential demand for librarians is also discussed
Keywords: Library schools